AB0793 Rheumatic Diseases with Emphasis in Osteoporosis in A Cohort of Patients with Breast Adenocarcinoma. (15th July 2016) - Hernández-Cruz, B.; González, P.; Leόn Rubio, P.; Lόpez, G.; Prieto, C.; Povedano Gόmez, J.
Abstract : Background: The osteoporosis (OP) and the breast cancer (BC) are diseases with increasing prevalence. The BC treatment includes total and early castration. In addition to surgical treatment and chemotherapy, they had lower levels of 25-OH-D vitamin, reduced physical activity and sun exposure, with effects in the bone health. Objectives: To know the prevalence of rheumatic diseases in a cohort of patients with BC attended in clinical practice in two hospitals. To identify the characteristics of the OP and their treatment. Methods: Setting: The Oncology Services and OP Unit of the Rheumatology Departments of the Hospital Virgen del Rocío (HUVR) and the Hospital Virgen Macarena (HUVM) in Seville, Spain. A prospective case series was design. Consecutive patients with BC who attended the Oncology Service (September to December of 2014) were evaluated. The patients were reviewed by 5 rheumatologists, previously trained about design, variables, data management, and the study protocol in order to collected 152 clinical variables. Descriptive statistics and univariate and multivariate statistics were done. The work was conducted in according to GPC and approved for the local ethical committee. Results: 151 patients were included, all them women. The mean age (p25-p75) was 64.3 years (40.0 – 81.2). The menopausal was at 48 (34–56) years; in 44% it was before than 45 years. There were 11% smokers; 34% with regular sun exposure; 5% on corticosteroids and 2% drinkers. The rheumatic diseases were: OP in 103 (68%), chronic musculoskeletal pain 16%, osteoarthritis 16%, fibromyalgia 9%. The most frequent comorbidities were depression (16%), hypothyroidism (9%), Secondary hyperparathyroidism 9%, and Diabetes (8%). The comorbidity Index (Charlson) was 2 (2–5). The mean OP duration was 3.3 (0.19 – 9.8) years. The OP diagnostic was done with FF in 26 (23%) cases, 7 of them without OP by BMD. The FF were vertebral in 15 (10%), peripheral in 10 (7%) and one case with both. The baseline FRAX was 5.1 (1.4 -26) for major FF and 1.3 (0.1 – 10) for hip FF. The OP was diagnosed with BDM of femoral neck in 31 (24%) and in total lumbar column in 57 (45%), and in both in 15 (12%). The patients were treated with Calcium plus 25-OH-VitD 89%, PO bisphosphonates 51%, denosumab 26%, IV bisphosphonates 11%, teriparatide 3%, and 36% received 25-OHVitD. None of the multiple regression models was able to predict FF. In the best of cases the models predicted 20% of the FF (R 2 ). The model with the FRAX as predictor of major FF was poor: R 2 0, 15, p<0, 0001; OR 1.15 (1.06 – 1.2). The FF were best predicted by the comorbidity index, SLE, RA or drinker; but with significant collinearity, and was impossible calculate statistics. Conclusions: Patients with BC had an elevated prevalence of rheumatic diseases and comorbidity. The OP was severe with a high prevalence of FF. The classical risk variables of FF cannot predicted it. In this group of patients, the FRAX was not a good tool of prediction. Disclosure of Interest: None declared